Pengaruh Literasi terhadap Perilaku Masyarakat Melakukan Utang Piutang dengan Norma Subjektif sebagai Variabel Moderating - Nurwahida, Nurwahida; Anwar, Nurfiah; Katman, Muhammad Nasri (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This research was cconducted with the aim of finding out the influence of literacy, in this case public knowledge about usury, on people’s behavior in carrying out debts and receivables with subjective norms as a moderating variable. The type of research used is quantitative research with a survey approach. The population, namely the total number of PNM Mekaar Mambi Branch costumers, wa 3.701 people. The sampel was determined using the kriccjie Morgan formula which then obtained 348 samples which were then used in this research. This research uses primary datta, namely direct responses from respondents via questionnaires distributed via Google form and distributing questionnaires directly the field. Data analysis was carried out using the SmartPLS 3 application. The results of the research show that literacy has a positive effect on people’s behavior in making debts and receivables.